T Source Inverter Based Shunt Active Filter with LCL Passive Filter for the 415V 50 Hz Distribution systems - S. Sellakumar; M. Vijayakumar (Institute of Advanced Engineering and Science, 2015)
The inverter topology is being used as an active filter to reduce the harmonics in the power system. The traditional voltage source or current source inverters are having the disadvantages of limited output voltage range hence it may not be able to supply enough compensating currents during heavy switching surges, Vulnerable to EMI noise and the devices gets damaged in either open or short circuit conditions and the main switching device of VSI and CSI are not interchangeable. The active filters are the type of DC-AC system with wide range of voltage regulation and integration of energy storages is often required. This cannot be achieved with conventional inverters and hence the impedance source inverters have been suggested. The T source inverters are basically impedance source inverters which can be used as an active filter in the power system. The MATLAB simulation is done and the results are discussed in this paper for both the types. The proposed dampening system is fully characterized by LCL based passive filters and T source inverter based shunt active filter. The disturbances in the supply voltage and load current due to the non linear loads are observed in the simulation. The same is studied after connecting the designed hybrid shunt active filter in the distribution system. The simulation results obtained from the proposed method proves that it gives comparatively better THD value.